HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN WANITA PEKERJA SEKSUAL TIDAK LANGSUNG TENTANG PAP SMEAR DAN IVA SEBAGAI DETEKSI DINI KANKER SERVIKS DI HOTSPOT X KECAMATAN PAYUNG SEKAKI PEKANBARU - Erwin Syahputra; Wiwit Ade Fidiawati; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is a malignant cell which lives in cervical cells. Cervicalcancer is in the second most common cancer after breast cancer in Indonesia.Based on the fact, indirect female sex worker have high risk factor of gettingcervical cancer. Only 5% of women in Indonesia who already have tested cervicalcancer early detection. The aim of this research is to find out the correlationbetween knowledge and attitude toward the action of indirect female sex workerabout Pap smears and IVA as the early detetction of cervical cancer in hotspot XPayung Sekaki district Pekanbaru. This research is conducted by using analyticcross sectional method and total sampling method for taking the sample and ituses questionnaire. There are 32 respondents in this research which most of themare lack of knowledge (78,1%), negative attitude (75%), and willing to do cervicalcancer early detection (96,9%). Writer finds that there is a correlation betweenthe knowledge toward the attitude (p=0,00). In other hands, there is nocorrelation between knowledge toward the act (p=0,607) and attitude toward theact (p=0,572). The conclusion of this research is most of the female sex worker inhotspot X Payung Sekaki district Pekanbaru have bad knowledge, negativeattitude, but have a positive practice towards servical cancer early detection.Keywords: knowledge, attitude, practice, indirect female sex worker